2016
DOI: 10.1093/mnras/stw1114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of the cluster pair: A3407 + A3408

Abstract: We carried out a dynamical study of the galaxy cluster pair A3407 & A3408 based on a spectroscopic survey obtained with the 4 meter Blanco telescope at the CTIO, plus 6dF data, and ROSAT All-Sky-Survey. The sample consists of 122 member galaxies brighter than m R = 20. Our main goal is to probe the galaxy dynamics in this field and verify if the sample constitutes a single galaxy system or corresponds to an ongoing merging process. Statistical tests were applied to clusters members showing that both the compos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Furthermore, the cluster properties r 500 , r 200 , and r 100 are consistent with the results of Nascimento et al (2016). In their dynamical analysis of 122 member galaxies of A3407 and A3408, the authors found galaxy velocity dispersions of σ A3407 = 718 +93 −48 km s −1 and σ A3408 = 573 +82 −59 km s −1 and corresponding virial masses of log(M V ) A3407 = 14.59 +0.46 −0.42 h −1 M and log(M V ) A3408 = 14.26 +0.55 −0.46 h −1 M .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the cluster properties r 500 , r 200 , and r 100 are consistent with the results of Nascimento et al (2016). In their dynamical analysis of 122 member galaxies of A3407 and A3408, the authors found galaxy velocity dispersions of σ A3407 = 718 +93 −48 km s −1 and σ A3408 = 573 +82 −59 km s −1 and corresponding virial masses of log(M V ) A3407 = 14.59 +0.46 −0.42 h −1 M and log(M V ) A3408 = 14.26 +0.55 −0.46 h −1 M .…”
Section: Discussionsupporting
confidence: 84%
“…Chow-Martínez et al ( 2014) classified A3408 and A3407 as a supercluster based on the small distance between the two neighboring clusters. Furthermore, there seems to be an indication that A3408 is interacting with A3407 (Nascimento et al 2016). Based on a dynamical study of 122 member galaxies, Nascimento et al concluded that A3408 and A3407 could be in a pre-merger scenario and might cross each other in less than ∼1 h −1 Gyr, or they might be in a post-merger scenario and might have crossed each other ∼1.65h −1 Gyr ago.…”
Section: Introductionmentioning
confidence: 99%
“…Galaxies identified as non-members using this method are shown in Figure 8 as black open circles. We note that the choice of σ200 as the maximum allowed gap is somewhat arbitrary, although it was found to produce good results here (see Figure 8), and in other clusters (e.g., Zabludoff et al 1990;Owers et al 2009aOwers et al ,b, 2011aNascimento et al 2016).…”
Section: Cluster Membership and Global Parametersmentioning
confidence: 69%
“…With the obtained lensing masses, this method allows us to estimate the probability that (1) the system is bound but still expanding, (2) the system is collapsing, or (3) the two structures are not bound to each other but are merely close together on the sky. It is important to highlight that this model does not consider the angular moment of the system, the distribution of matter inside each cluster, or the gravitational interaction of the infalling matter outside the cluster pair, since it is assumed that the masses are constant since their formation time (Nascimento et al 2016). Nevertheless, this model puts another constraint on the dynamical state and the evolution of the systems.…”
Section: Two-body Modelmentioning
confidence: 99%